CRIME OF ABORTION STUDY IN INDONESIA - Frans Simangunsong (Faculty of Law Universitas 17 Agustus 1945 Semarang, 2017)
Abortion is a social phenomenon that is increasingly alarming. The concern is not without reason, because so far the behavior of abortion many negative effects both for themselves perpetrators and the community at large. In terms of positive law in Indonesia, there is still debate and opposition from the pros and cons about the perception or understanding of the laws that exist to this day. Neither of Health Law, the Law on medical practice, The Criminal Code (Penal Code), Law on the elimination of domestic violence (domestic violence), and the Law on Human Rights (HAM). Normative legal research(normative law research) using the product in the form of case studies of normative legal behavior. Factors that led to the crime of abortion is rampant in Indonesia, partly because the sex education curriculum(sex education)in schools has been less effective in tackling promiscuity among teenagers. Therefore, the role of parents is very important in instilling moral values, ethics, law and religion. Sexual promiscuity among teenagers Indonesia today is alarming. Efforts to tackle the crime of abortion in the study of law in Indonesia. As for things - things that must be done by governments, institutions, communities and families in tackling illegal abortions are: Government: Providing spectacle qualified educate and prohibit the spectacle that does not make sense and did not educate as patron wearing tight uniform, Soon follow-up of cases - cases of illegal abortion and impose penalties sufficient to deter; Society: Society as a social institution should be more sensitive control and participate on everything that exists within its territory, reinforcing the social control in society